The Effect Of 5-Finger Hypnosis Therapy on Reducing Anxiety Levels in Preoperative Patients in The Surgical Clusterisation Inpatient Room of The Workers' General Hospital - Mahyar Suara (Jurnal Penelitian Pendidikan IPA, 2025)
Surgery is a treatment method that uses invasive techniques, by making an incision to open and display the part of the body to be treated, then closing the wound with a suturing process. The impact of surgery can cause various psychological problems in patients, one of which is anxiety. Therapy to reduce anxiety is five-finger hypnosis therapy, a self-hypnosis method that can provide a high relaxation effect, thereby helping reduce tension and stress in the mind. The aim of this study was to determine the effect of providing 5 finger hypnosis therapy on reducing anxiety levels in pre-operative patients in the Clustered Surgical Inpatient Room at the Workers' General Hospital. This type of research is quantitative descriptive research. This research uses a quasy experiment with a pre- post approach without control. The sample used with respondents was 18 respondents. The research instrument used in this research was the HARS questionnaire which the author created and provided closed questions. Data collection was carried out using primary data. Data analysis uses univariate analysis and bivariate analysis. The results of the paired t-test statistical test show the p value = 0.000, meaning the p value < alpha value (0.05), thus the decision is that Ho is rejected and Ha is accepted. The conclusion is "There is a significant effect of 5 finger hypnosis therapy on reducing anxiety levels in pre-operative patients in the Clustered Surgical Inpatient Room at the Workers' General Hospital. Thus, 5 finger hypnosis therapy needs to be applied to pre-operative patients so that anxiety can be reduced.